An Animation-Enhanced Presentation for Illustrating Hormonal and Metabolite Regulation of Metabolic Pathways in the Context of Diabetes - Eric Niederhoffer (Association of American Medical Colleges, 2014)
Abstract Introduction This resource is an unscripted presentation enhanced with animations that is designed to illustrate the role of insulin, glucagon, cortisol, epinephrine, and adenosine monophosphate-activated protein kinase along with selected metabolites in regulating specific steps in glycogenesis, glycogenolysis, glycolysis, gluconeogenesis, lipogenesis, and lipolysis. This resource is designed to fit within a 90 to 105-minute session with one or two short breaks. A series of slides are used to discuss individual hormones followed by a slide containing all of the hormonal and metabolites effects. Notes are provided for each slide of the presentation containing information that may be incorporated into the narrative or used by the students without discussion during the presentation. A series of impact slides reiterate the effects of insulin deficiency on each metabolic pathway and a final summary slide contains questions that focus on the key hormones, metabolites, enzymes, and tissues. Methods The submission contains a PowerPoint file that contains the presentation and can be modified and updated as appropriate. A DeltaGraph file contains data used to construct the glucose homeostasis graph that appears in the presentation and can be modified for future use. There is also an image of the data for individuals lacking the DeltaGraph application. Results This presentation has been used and evaluated over a period of 4 years with consistent numerical scores. A majority of students agreed or strongly agreed that the sessions provided a helpful supplement to their self-directed learning on the cases. Discussion Although written comments were overall very positive, but there were comments suggesting that the slides contained too much information (too many hormones put together). As a result, the presentation was modified in 2013 to break out separate slides containing individual hormones and a composite slide with all the hormones for each metabolic pathway. Specific comments were solicited from the students to address this change. The consensus comment was that the presentation was very helpful and providing separate slides of the role of insulin and glucagon in individual pathways was very much appreciated.